2011
DOI: 10.1038/ja.2011.65
|View full text |Cite
|
Sign up to set email alerts
|

Antimycins A19 and A20, two new antimycins produced by marine actinomycete Streptomyces antibioticus H74-18

Abstract: Two new antimycin antibiotics, that is antimycins A 19 (1) and A 20 (2), were isolated from a cultured broth of marine actinomycete Streptomyces antibioticus H74-18 together with antimycins A 1a (3a) and A 1b (3b), A 2a (4), A 3a (5a) and A 3b (5b). Their structures were determined by spectroscopic methods in combination with X-ray diffraction. Antimycin A 19 possessed a chiral acyl chain and an alkyl branch. The absolute configuration of chiral acyl chain in 1 was determined by X-ray diffraction analysis. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Antimycin B1 ( 39 ) was inactive against the bacteria Bacillus subtilis , Staphyloccocus aureus and Loktanella hongkongensis , but antimycin B2 ( 40 ) showed antibacterial activities against S. aureus and L. hongkongensis with MIC values of 32.0 and 8.0 μg/mL respectively. Two new compounds antimycin A19 ( 41 ) and A20 ( 42 ) were isolated from Streptomyces antibioticus H74-18 in the bottom soil of the mangrove zone in the south China sea and these compounds showed antifungal activities against Candida albicans with MIC of about 5–10 μg/mL [59]. In 2011 total synthesis of the (+)-antimycin A family was reported and the nine-membered dilactone ring was obtained successfully by lactonization of a 2-pyridinethiol ester bearing a TIPS group on the 8-OH [60].…”
Section: Natural Products Produced By Mangrove Actinomycetesmentioning
confidence: 99%
“…Antimycin B1 ( 39 ) was inactive against the bacteria Bacillus subtilis , Staphyloccocus aureus and Loktanella hongkongensis , but antimycin B2 ( 40 ) showed antibacterial activities against S. aureus and L. hongkongensis with MIC values of 32.0 and 8.0 μg/mL respectively. Two new compounds antimycin A19 ( 41 ) and A20 ( 42 ) were isolated from Streptomyces antibioticus H74-18 in the bottom soil of the mangrove zone in the south China sea and these compounds showed antifungal activities against Candida albicans with MIC of about 5–10 μg/mL [59]. In 2011 total synthesis of the (+)-antimycin A family was reported and the nine-membered dilactone ring was obtained successfully by lactonization of a 2-pyridinethiol ester bearing a TIPS group on the 8-OH [60].…”
Section: Natural Products Produced By Mangrove Actinomycetesmentioning
confidence: 99%
“…Antimycins A 19 and A 20 (antimycin antibiotics), which inhibited C. albicans with an MIC of about 5–10 µg/ml, were isolated from a culture broth of marine actinomycete Streptomyces antibioticus H74-18 (Xu et al 2011a). …”
Section: Antifungal Productsmentioning
confidence: 99%
“…Molecular studies showed that these compounds could inhibit the mitochondrial electron transport chain between cytochromes b and c [9]. To date, 20 antimycin A compounds have been reported [10]. A recent report analyzing the biosynthetic gene clusters of antimycin A from Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%